2018
DOI: 10.1111/bjd.16267
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoedema in patients with lentigo maligna treated with imiquimod: a long-term adverse effect

Abstract: DEAR EDITOR, Lentigo maligna (LM) is a potential precursor lesion of lentigo maligna melanoma (LMM). It is treated to prevent progression to LMM. A recent epidemiological study reports a progression rate of 2Á0-2Á6% over the course of 25 years.1 The gold standard treatment is surgical excision with a 5-mm margin. 2 Topical application of imiquimod

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As there are no effective therapeutic strategies available to improve early treatment T. gondii infection, the development of new anti-Toxoplasma drugs should have high priority to tackle toxoplasmosis and reduce infection. Imidazoquinoline compounds such as imiquimod work as immune response modifiers with antiproliferative, antiparasite, antifungal, and antiviral activities that have been examined in several previous studies (van der Fits et al, 2009;de Sousa et al, 2014;Tio et al, 2018;Jabari et al, 2019). The cytotoxic effect of imiquimod against various cancers has been investigated, and it was shown that it induces apoptosis as well as increasing levels of the opioid growth factor receptor (OGFr) (Wybran and Plotnikoff, 1991;Zagon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As there are no effective therapeutic strategies available to improve early treatment T. gondii infection, the development of new anti-Toxoplasma drugs should have high priority to tackle toxoplasmosis and reduce infection. Imidazoquinoline compounds such as imiquimod work as immune response modifiers with antiproliferative, antiparasite, antifungal, and antiviral activities that have been examined in several previous studies (van der Fits et al, 2009;de Sousa et al, 2014;Tio et al, 2018;Jabari et al, 2019). The cytotoxic effect of imiquimod against various cancers has been investigated, and it was shown that it induces apoptosis as well as increasing levels of the opioid growth factor receptor (OGFr) (Wybran and Plotnikoff, 1991;Zagon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] (2018) CR 1 1 69 LM: cheek 1 Partial surgical excision + imiquimod 5% once/d 3 t/w for 3 m (only 15 applications because of inflammation) NR Complete (H) 5 y 0 (C) Tio et al . [ 31 ] (2018) CS 3 3 66–69 μ = 68 LM: cheek H Imiquimod 5% once/d 7 t/w for 8 w If insufficient response: Imiquimod 5% up to 3 t/d 7/w If exaggerated inflammatory response: imiquimod 5% once/d 3 t/w 1–2 Complete (H) NR NR Veraitch et al . [ 100 ] (2018) CR 1 1 75 MIS: vulva H Imiquimod 5% once/d once/w for 8 w then twice/w for 18 m NR Partial (H) NR NR Hamilko de Barros et al .…”
Section: Resultsmentioning
confidence: 99%
“…The most common adverse effects are local erythema, burning, edema, and crusts [ 30 ]. The development of alterations in skin pigmentation, such as post-inflammatory hyper and hypopigmentation, are also possible [ 31 ]. In their study, Di Bartolomeo et al observed the formation of perifollicular blue gray dots after 12 weeks of treatment with imiquimod 5% [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug may also cause side effects at non-application sites such as flu-like systemic syndrome or distant inflammatory mucosal reactions [ 26 ]. Some long-term adverse effects have been described, such as vitiligo-like depigmentation, associated with the mechanism of the action of imiquimod [ 27 ], and lymphoedema, caused by severe inflammation and dermal fibrosis [ 28 ].…”
Section: Immunotherapy In Melanoma In Situmentioning
confidence: 99%